Aligning AI Impact with Strategy: Cross Sector Metrics for Sustainable Business Model Transformation - Meutia, Kardinah Indrianna (Indonesian Scientific Publication, 2024)
AI-enabled Business Model Innovation (BMI) has become a key driver of competitive advantage. This study explores the role of standardized and adaptive metrics in assessing AI’s strategic and operational impacts across industries. Drawing on literature reviews, sectoral case studies, and industry surveys, the findings show that universal metrics support broad comparability, while sector-specific measures capture operational nuances. A hybrid framework integrating universal KPIs, sectoral extensions, and adaptive dimensions for evolving AI capabilities is proposed to ensure relevance, reliability, and social alignment. AI-driven operational improvements gain higher business value when combined with adaptive monetization models and supported by ethical and trust-based metrics. Thus, developing dynamic and context-aware performance measurement frameworks is a strategic necessity in the era of intelligent enterprises.